From trauma to healing : a social worker's guide to working with survivors - Goelitz, Ann (New York, NY : Routledge, 2021)
"This updated edition of From Trauma to Healing is a comprehensive and practical guide to working with trauma survivors in the field of social work. With fresh examples and discussion questions to help deal with traumatic events in practice, including interventions that may be applicable to current and future 21st century world events, such as the coronavirus pandemic, From Trauma to Healing, 2nd edition remains an essential publication on trauma for students and social workers alike"--
OCLC-licensed vendor bibliographic record.
Keywords: Psychiatric social work; Mentally ill -- Services for; Psychic trauma -- Treatment; MEDICAL / Mental Health; PSYCHOLOGY / Mental Health; SOCIAL SCIENCE / Social Work